Conclusions and Directions for Future Work - Doreian, Patrick; Ferligoj, Anuška; Batagelj, Vladimir (Advances in Network Clustering and Blockmodeling, 2020)
This conclusion presents some closing thoughts on the concepts covered in the preceding chapters of this book and makes additional suggestions regarding potential future work. The book presents a wide variety of approaches and methods related to network clustering. It suggests that the institutional structure of science has a very large impact on the generation of scientific knowledge and the generation of scientific citation networks. The book advocates the optimization approach to the clustering problem. Using an appropriate criterion function, people can express their clustering goals, including the reduction of complexity, understanding network structures, and modeling networks. Together, optimization and the sought goals help define the nature of a “good” clustering. The book finishes by stressing two very general ideas. One is the importance of the exchange of ideas between different approaches with the goal of strengthening them. The second is the coupling of network processes and network structures to help readers understand both.